Digital watermarking techniques and methodologies - Khalifa, Othman Omran; Yusof, Yusnita (IIUM Press, 2011)
Digital watermarking is a huge research area which is progressively growing. It covers theoretical studies. novel techniques, attacks and performance analysis. Over the years, the digital watermarking community has focused on developing new techniques for watermark embedding and detection. Analysis of these techniques leads to methods for attacks and countermeasures which are used to discover faults and limitations in applications, encouraging the development of better ones. Digital watermarking is distinctive depending on its techniques and applications. The location of watermark embedding determines two kinds of methods:- The spatial domain methods embed watermark information directly into images pixels. On the other hand, the frequency domain methods embed watelmark information in the transform domain. The general approach used in these methods is to divide the image into blocks. Each block is mapped into the transform domain using either the Discrete Cosine Transform (DCT) [9], the Discrete Fourier Transform (DFT), or the Wavelet Transform. Embedding the watermark in the frequency domain can provide more robustness than in the spatial domain. It is strong against attacks like compression where spatial domain is not. Image watermarking techniques can be distinguished according to the way the watermark is revealed from the watermarked image. One way is by comparing this image to the original one, while the other doesn't resort to this comparison. The second are usually refen'ed to as blind watermarking techniques and are preferable.